A Review on Vibration Analysis of Seismocardiography (SCG) - Seng Hooi, Ng.; Bin Ismail, Kamarulafizam; Mailah, M.; Rizman, Md. (International Journal of Engineering and Technology, 2018)
This paper reviews on the non-invasive cardiac diagnostic method using accelerometer. Currently, the clinical cardiac diagnostic tools that are available are acoustic stethoscope, electrocardiogram (ECG) and echocardiography. The ECG represents cardiac electrical activities that provide important information to diagnose diseases such as myocardial ischemia, infarction and arrhythmias. However, it is not very helpful to diagnose cardiac contractility dysfunction and valvular diseases. Echocardiography provides alternative solution to the problem. Based on the principle of ultrasound imaging, it can precisely capture the heart images that works in real-time. Nevertheless, it comes with high operational cost and requires a specialist who is an expert and properly trained. It is also not immediately available in most hospital and medical institutions. This review will emphasize on the technological trends of devices that are able to capture heart related diseases. The usage of accelerometer has gained lots of attention as its ability to detect micro-vibration is outstanding. It is placed on the surface of the chest and listens to the vibrations, which are produced by the operations of the valves. The ability to pick up such information somehow depends on many factors such as the sensor sensitivity, the sensor placement method, position and the extraction algorithm used. Each of these factors will be discussed and compared.Â Â Â